Profile of construction industry workforce in Juazeiro do Norte, Brazil (Research, Society and Development, 2020)
The construction industry sector is characterized by presenting an archaic approach to the constructive practices applied at the construction site, generating unfavorable indicators in terms of quality and productivity. Thus, a greater concern arises regarding the training and qualification of the workforce, historically known for its low schooling and qualification, hindering the elaboration and application of technological innovations and the use of modern constructive techniques. The aim of this study is to analyze the profile of construction workers in the municipality of Juazeiro do Norte, seeking information related to age, marital status, city of residence, education, level of qualification, function exercised and time of operation in the sector. Regarding the methodology, we opted for the inductive method, and a field research was carried out, using a questionnaire to collect data applied in five works of medium and small construction companies installed in the city of Juazeiro do Norte - CE, with a sample of 100 workers. The results indicate that 55% of the construction workers analyzed in this study are older than 35 years, in addition to a low renewal of the staff, low level of education and their knowledge occurred empirically, besides low interest in vocational courses. It was found that 100% of the workforce is male, the predominant age group is 30 to 39 years, most are married and with children, with origin of the city itself, the level of education of the workers is still considered low, but only 8% of the workers are considered illiterate, the average time of performance is more than 10 years and 94% of them reported that they learned the constructive techniques in practice or with relatives.